‘We do not like talking about our problems’: socialization and idealized masculinity as drivers of help-seeking avoidance among college men in South Africa - Sikweyiya, Yandisa; Jewkes, Rachel; Machisa, Mercilene (BioMed Central, 2025)
Background: This article explores how identities and contexts influence help-seeking avoidance behaviour among college men. Methods: This exploratory qualitative study purposively selected 88 male students (aged 18–30) from some universities and Technical and Vocational Training colleges (TVETs) in South Africa. Data were collected through focus group discussions (FGDs). Eight FGDs were conducted, one in each selected university (n = 2) and TVETs (n = 6) in 2018–2019. Data were analyzed using a thematic analysis approach. Results: We found that college men’s early life experiences and socialisation strongly influenced their ability to express emotion and access services when in need of help. The data also revealed a masculinity that men aspired to and wanted to be seen as embracing or personifying while on campus. Most men ascribed to an ideal of masculinity that made it difficult for them to share their feelings (e.g., emotional pain, sadness; and bottle their emotions) and seek help from campus-based counselors or peers. The few men who reported using campus mental health support services appraised them as unsuitable and unhelpful for them, and indicated a preference for services that were more culturally relevant. Most men indicated a preference for male counselors, of which there were very few. Conclusions: These findings may be useful for the formulation of evidence-based context-specific and culturally sensitive approaches for increasing men’s access to mental health and psychological support services on South African college campuses.
Keywords: College men; Gender-transformative programming; Help-seeking avoidance; Masculinities; Mental health promotion; SDG-3: Good health and well-being